The Subiculum: A Potential Site of Ictogenesis in a Neonatal Seizure Model - Wang, Xin-Xin; Li, Yong-Hua; Gong, Hai-Qing; Liang, Pei-Ji; Zhang, Pu-Ming; Lu, Qin-Chi (Frontiers in Neurology, 2017)
Studies have reported that the subiculum is one origin of interictal-like discharges in adult patients with temporal lobe epilepsy; however, whether the subiculum represents a site of ictogenesis for neonatal seizures remains unclear. In this study, multi-electrode recording techniques were used to record epileptiform discharges induced by low-Mg2+ or high-K+ artificial cerebrospinal fluid in neonatal mouse hippocampal slices, and the spatiotemporal dynamics of the epileptiform discharges were analyzed. The Na+-K+-2Cl- cotransporter 1 (NKCC1) blocker, bumetanide, was applied to test its effect upon epileptiform discharges in low-Mg2+ model. The effect of N-methyl-D-aspartate receptors (NMDARs) antagonist, D-AP5, upon the epileptiform discharges in high-K+ model was examined. We found that the neonatal subiculum not only relayed epileptiform discharges emanating from the hippocampus proper, but also initiated epileptiform discharges (interictal- and ictal-like discharges) independently. The latency to onset of the first epileptiform discharge initiated in the subiculum was similar to that initiated in the hippocampus proper. Bumetanide efficiently blocked seizures in the neonatal hippocampus proper, but was less effectively in suppressing seizures initiated in the subiculum. In high-K+ model, D-AP5 was more effective in blocking seizures initiated in the subiculum than that initiated in the hippocampus proper. Furthermore, Western blotting analysis showed that NKCC1 expression was lower in the subiculum than that in the hippocampus proper, whereas the expression of NMDAR subunits, NR2A and NR2B, was higher in the subiculum than that in the hippocampus proper. Our results revealed that the subiculum was a potential site of ictogenesis in neonatal seizures and possessed similar seizure susceptibility to the hippocampus proper. GABAergic excitation resulting from NKCC1 may play a less dominant role during ictogenesis in the subiculum than that in the hippocampus proper. The subicular ictogenesis may be related to the glutamatergic excitation mediated by NMDARs.